REACTIVE ARTHRITIS: LITERATURE REVIEW, TARGET TREATMENTS IN THE ERA OF BIOLOGICS - Javohir Mullokulov; Khalmurad Sadullayevich Akhmedov; Feruza Iskandarovna Khalmetova (Journals Park Publishing, 2024)
Reactive arthritis (ReA) is an autoimmune condition characterized by joint inflammation that typically arises following an infection, most commonly in the gastrointestinal or genitourinary tract. It is considered part of the broader spectrum of spondyloarthropathies, with hallmark symptoms including asymmetric arthritis, enthesitis, and dactylitis, often involving the lower limbs. The condition is triggered by bacterial infections, such as Chlamydia trachomatis, Salmonella, or Campylobacter, although the exact pathogenic mechanisms remain unclear. Reactive arthritis may manifest as acute, self-limiting inflammation, or progress to a chronic condition, leading to prolonged disability and joint damage in severe cases.[1]. This review explores the clinical presentation, pathophysiology, diagnostic criteria, and treatment strategies for ReA. Therapeutic interventions range from nonsteroidal anti-inflammatory drugs (NSAIDs) for pain management to disease-modifying antirheumatic drugs (DMARDs) and biologic agents like TNF inhibitors for persistent and severe cases. Recent advances in understanding the molecular mechanisms, particularly the role of HLA-B27 and cytokine dysregulation, offer new insights into potential therapeutic targets. Early diagnosis and appropriate management are crucial for preventing long-term complications and improving patient outcomes. This article also discusses emerging treatments and the challenges of managing ReA in the context of coexisting infections and chronic disease.[2].
Keywords: HLA-B27, Reactive arthritis, TNF inhibitors, JAK inhibitors.